Review of Natural Fiber Reinforced Epoxy Resin Composite Materials for Automotive Component Applications - Suharmadi, Suharmadi -; Fitri, Muhammad (Universitas Mercu Buana, 2026)
Epoxy resin is a thermosetting polymer widely used in composite materials due to its high mechanical strength, excellent chemical resistance, and strong adhesion. In composite structures, epoxy acts as a matrix that binds and protects the reinforcing fibers while transferring loads between components. The reinforcing fibers may be synthetic (e.g., fiberglass, carbon) known for their high tensile strength, or natural fibers (e.g., kenaf, ramie), which offer advantages in sustainability and low weight. With the growing demand for lightweight, efficient, and environmentally friendly automotive materials, epoxy-based composites show significant potential for use in body panels, interior parts, and structural vehicle components. However, challenges remain, such as poor interfacial bonding between epoxy and natural fibers, thermal degradation, and relatively high production costs. This study aims to systematically review current research trends, applications, and research gaps in the development of epoxy resin composites for automotive components, particularly those reinforced with natural fibers. The method used is a Scoping Review based on the PRISMA-ScR framework, covering 50 scientific articles published between 2015 and 2025. The results indicate that kenaf, ramie, and jute fibers have strong potential as sustainable reinforcements, although improvements in interfacial compatibility and processing technology are still critical. The study implies the importance of advancing bio-based epoxy resins, hybrid manufacturing techniques, and the utilization of local natural fibers as part of a sustainable automotive strategy